Review of Jean-Luc Nancy. 2007. Listening. Translated by Charlotte Mandell. New York: Fordham University Press - Gallope, Michael (Current Musicology, 2008)
After years and years of debate, has music studies come to a consensus on how to relate culturalist and historicist claims about music to formal claims? Or are most analytical approaches still to external to musical experience? In Charlotte Mandell’s splendid translation of Jean-Luc Nancy’s brief but passionate À l’écoute, the French philosopher gives us a glimpse of a completely different philosophy of music. Uninterested in wresting out the dialectic between immaterial structure and the materiality of a self-evident cultural practice, Nancy’s notion of music in Listening (as Mandell has translated in À l’écoute) respects no proper distinction between subject (listeners, participants, composers, musicians, or otherwise) and object (say, a thing or phenomenon of organized sound). Nancy prefers to think of music as the becoming-sound of sense; this means his book is not so much a “philosophy of music” in the regular sense of the phrase as it is a philosophy of listening.